2021
DOI: 10.1186/s12885-021-08121-y
|View full text |Cite
|
Sign up to set email alerts
|

A prospective interventional study evaluating seizure activity during a radiotherapy course for high-grade gliomas (SURF-ROGG)

Abstract: Background Gliomas are often associated with symptoms including seizures. Most patients with high-grade gliomas are treated with radiotherapy or radio-chemotherapy. Since irradiation causes inflammation, it may initially aggravate symptoms. Studies focusing on seizure activity during radiotherapy for gliomas are not available. Such knowledge may improve patient monitoring and anti-epileptic treatment. This study evaluates seizure activity during radiotherapy for high-grade gliomas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…However, extensive investigations have not yet been reported for GBM and therefore, seizure outcomes may differ. A prospective interventional trial evaluating the effect of RT on seizure activity in high grade (IV) gliomas is currently ongoing (Rades et al, 2021 ). Results from this study will aid understanding and inform future decisions pertaining to the application of individual anti-tumorigenic treatments in GBM patients with seizures.…”
Section: From Laboratory To Clinical Translationmentioning
confidence: 99%
“…However, extensive investigations have not yet been reported for GBM and therefore, seizure outcomes may differ. A prospective interventional trial evaluating the effect of RT on seizure activity in high grade (IV) gliomas is currently ongoing (Rades et al, 2021 ). Results from this study will aid understanding and inform future decisions pertaining to the application of individual anti-tumorigenic treatments in GBM patients with seizures.…”
Section: From Laboratory To Clinical Translationmentioning
confidence: 99%
“…The efficacy analysis will be performed on the modified Full Analysis Set defined as all patients receiving radiotherapy with a completed questionnaire at baseline and at least one completed questionnaire after start of treatment. Similar to a previous study, the statistical analyses are mainly descriptive and exploratory [ 10 ]. Sleep disorders at baseline and during radiotherapy will be rated using two patient self-reporting scales (sleep disorders and distress) and intake of sleeping drugs.…”
Section: Objectives and Endpointsmentioning
confidence: 99%
“…Similar to a previous study, patients can be identified only by an individual number and their month/year of birth [ 10 ]. Data will be handled in accordance with the General Data Protection Regulation and German regulations for radio-protection.…”
Section: Objectives and Endpointsmentioning
confidence: 99%
“…The study received approval by the ethics committee of the University of Lübeck, Germany (reference 20-311) and was registered at clinicaltrials.gov (identifier: NCT04552756). Eligibility criteria were previously reported and included histologically proven grade III or IV glioma, indication for normo-fractionated radiotherapy, Eastern Cooperative Oncology Group performance score of 0-2, age ≥18 years, written informed consent, and the patient's capacity to cooperate and keep the seizure diary (13).…”
mentioning
confidence: 99%
“…Radiotherapy was performed as volumetric modulated arc therapy. Further details of radiation treatment were previously described (13). Planned regimens included 59.4 Gy in 33 fractions of 1.8 Gy in 17 patients (77%) and 60 Gy in 30 fractions of 2.0 Gy in 5 patients (23%).…”
mentioning
confidence: 99%